Vocalizations by red fox (Vulpes vulpes) in natural and climatic conditions of Mordovia (Middle Volga region) - Andreychev Alexey (E3S Web of Conferences, 2023)
The daily and seasonal vocalization of the red fox was traced. Year-round studies were carried out using digital voice recorders. Fox barking was recorded in the frequency range from 700 to 3600 Hz. The cackling of the fox was recorded in the frequency range from 500 to 2500 Hz. Fox calls were recorded in all seasons of the year, but the most pronounced peaks of prolonged activity in the year were recorded in spring and autumn. The vocal activity of the red fox was noted for the entire period of the study from 17:51 to 01:38. During this period, the total duration of calls in the red fox varied from 34 sec to 27 min per day, 4 min on average. 86% of all call registrations in the region occurred before midnight, the rest (14%) after midnight. Vocalization began after sunset for an average of 2 h 49 min.